Penerapan Forward Chaining pada Sistem Informasi Diagnosa Penyakit Berbasis WEB Menggunakan Metode Rapid Application Development - Maysa Aulia Salsabila; Mukh Taufik Chulkamdi; Mohammad Faried Rahmat (Program Studi Teknik Informatika Universitas Nusa Putra, 2024)
The complexity of diagnosing diseases in children and adults has resulted in many types of drugs with different characteristics, often confusing the general public in differentiating drugs based on symptoms. For example, coughs with phlegm and non-phlegm are often considered the same, even though they require different treatment. This research uses the Forward chaining method in a web-based disease diagnosis information system using the Rapid application development (RAD) method to help people recognize disease symptoms more accurately. This system was developed using PHP and MySQL. Forward chaining testing shows results of 80%, while black box testing produces 100%, indicating that all system functions are running well. Apart from that, the open beta results from midwives and the community reached 88.32%, indicating that the system is suitable for use. Security testing also shows optimal results, with a score of 100% for password trial restrictions, SSL, and automatic backup using cron jobs. The results of the close beta test by users obtained a score of 90.37%, which indicates that this system is very feasible to implement. This research was conducted at dr. general Arsinta, Jl. Mosque No. 20, Sananwetan, Blitar City.